Filtration Efficiency of Intermediate Ventilation Air Filters on Ultrafine and Submicron Particles - Diez Maroto, Maria (My University, 2011)
A number of recent epidemiological studies have addressed the association of mortality or morbidity of urban populations with ambient submicron and ultrafine particle concentrations. Evaluating the filtration efficiency of intermediate filters on submicron and ultrafine particles is motivated by increasing public concern on indoor air quality in commercial and residential buildings. The present study is focused on filtration efficiency testing of full-scale fibrous filters of the intermediate (fine) filter classes F5-F9. Special attention has been paid to submicron and ultrafine particles, in experiments conducted in the laboratory of Building Services Engineering, Chalmers University of Technology. A Scanning Mobility Particle Sizer (SMPS) spectrometer was utilized in the test process. The filters were challenged by DEHS aerosol and NaCl aerosol. The tested intermediate bag filter modules are commonly applied, not only in Sweden, but also internationally. This study systematically researches the filtration efficiency of new intermediate ventilation air filters on submicron and ultrafine particles under the standard test conditions specified in the European standard EN779. It provides important reference data to evaluate the protection capacity of intermediate filters to submicron and ultrafine particles. Furthermore, the study also investigates the influence of air flow rate, filter material, and challenge aerosol on the test results. A separate set of tests was conducted to study the influence from using a neutralizer in order to change the electrostatic properties of the aerosol. The investigation is intended to provide background information when discussing possible improvements of the current standards for filter testing and classification.
Keywords: Building Futures; Byggnadsteknik; Building Futures; Building engineering